DIGITALISASI INSPEKSI ALAT PROTEKSI KEBAKARAN BERBASIS QR CODE DENGAN PENDEKATAN PDCA - Tegar Rizky Setiawan; Agus Suwarno; Annisa Syahliantina (Journal of Industrial Engineering & Technology Innovation, 2026)
Fire is one of the main risks in industrial environments that can cause significant losses. PT XYZ has 185 fire protection devices, with fire extinguishers (APAR) and hydrants as the primary components totaling 62 units. Observations revealed that 17 of 51 APAR units (33%) and 3 of 11 hydrant units (27%) were in substandard condition, caused by a manual inspection system with weaknesses including paper-based data vulnerable to loss, lack of centralized monitoring, difficulty tracing inspection history, no expiry reminders, and slow data compilation. This study aims to analyze the actual condition of fire protection equipment, evaluate inspection compliance, and implement a QR Code-based digital inspection system using the Plan Do Check Act (PDCA) method. Simulation on 15 APAR units and 5 hydrant units demonstrated a 35% time efficiency improvement, reducing inspection time from 71 to 46 minutes. The digital system outperformed the manual system across all evaluation indicators. The estimated full implementation cost for 62 units is IDR 2,248,000, considered proportional to the risks of fire protection system failure